Silício como mitigador de deficiências nutricionais em plantas de sorgo - Simogaki, Maila [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Sorghum is a crop of great economic importance, being cultivated mainly due to its high adaptability to conditions of low soil fertility. However, cultivation in these areas can induce nutritional deficiencies in the crop, limiting its initial development with repercussions on the decrease in production. A strategy to improve crop productive performance and fertilization efficiency is the addition of (Si), a beneficial element that mitigates damage caused by abiotic stresses, such as nutritional deficiencies. The objective of this work was to evaluate the damage caused by macronutrient deficiency in the initial growth of sorb plants, as well as whether Si is efficient in mitigating these deficiencies. The treatments consisted of a scheme in a factorial scheme of 7 x 2, being the first factor consisting of the supply of a complete solution (SC) of Hoagland and Arnon (1950) and others with the same solution but with the suppression of macronutrients, with absence of nitrogen (-N), phosphorus (-P), potassium (-K), calcium (-Ca), magnesium (-Mg), sulfur (-S) and more control (all nutrients); and the second factor consisting of the supply of Si: absence (-Si) and presence (+Si). The experimental design used was randomized blocks with six replications. Si was added to the nutrient solution using the concentration of 2.0 mmol L-1. Si accumulation in shoots and roots, quantum efficiency of photosystem II, stem diameter, plant height, shoot and root dry mass were evaluated. The supply of Si provided an increase in the accumulation of the element in the shoots and roots. The nutrients that most limited dry mass production in plants in the initial phase of development of sorb plants grown in the absence of Si were N and Ca. However, Si in the cultivation solution was efficient to mitigate the damage caused by nutritional deficiency only of P and Ca.

O sorgo é uma cultura de grande importância econômica, sendo cultivo principalmente devido a sua elevada adaptabilidade a condições de baixa fertilidade de solo. No entanto, o cultivo nessas áreas pode induzir deficiências nutricionais na cultura, limitando o seu desenvolvimento inicial com reflexos na diminuição da produção. Uma estratégia para melhorar o desempenho produtivo da cultura e a eficiência das adubações é a adição de (Si), um elemento benéfico que atenua os danos causados por estresses abióticos, como as deficiências nutricionais. O objetivo desse trabalho foi avaliar os danos causados pela deficiência de macronutrientes no crescimento inicial de plantas de sorgo, bem como, se o Si é eficiente na mitigação dessas deficiências. Os tratamentos consistiram em um esquema fatorial de 7 x 2, sendo o primeiro fator constituído pelo fornecimento de uma solução completa (CS) de Hoagland and Arnon (1950) mais omissões dos seguintes macronutrientes: nitrogênio (-N), fósforo (-P), potássio (-K), cálcio (-Ca), magnésio (-Mg) e enxofre (- S); e o segundo fator, constituído pelo fornecimento de Si: ausência (-Si) e presença (+Si), na concentração de 2,0 mmo L-1 . O delineamento experimental utilizado foi o de blocos ao acaso com seis repetições. Foram avaliados o acúmulo de Si na parte aérea e nas raízes, eficiência quântica do fotossistema II, diâmetro do caule, altura da planta, massa seca da parte aérea e das raízes. O fornecimento de Si proporcionou aumento do acúmulo do elemento na parte aérea e nas raízes. Os nutrientes que mais limitaram a produção de massa seca em plantas na fase inicial de desenvolvimento de plantas de sorgo cultivadas na ausência de Si foram o N e o Ca. No entanto, o Si na solução de cultivo foi eficiente para mitigar os danos causados pela deficiência nutricional apenas de P e Ca.
Silicon as a mitigator of nutritional deficiencies in sorghum plants
Keywords: Deficiências; Sorgo; Adubos e fertilizantes; Elementos traços na nutrição de plantas; Nutrientes; Adubos e fertilizantes; Plantas Nutrição